2021
DOI: 10.1016/j.heliyon.2021.e07353
|View full text |Cite
|
Sign up to set email alerts
|

Communication protocols evaluation for a wireless rainfall monitoring network in an urban area

Abstract: Rainfall monitoring networks are key elements for the development of alerts and prediction models for communities at risk of flooding during high intensity rainfall events. Currently, most of these networks send the precipitation measurement to a data center in real-time using wireless communication protocols, avoiding travel to the measurement site. An Early Warning System (EWS) for pluvial flash floods developed in Barranquilla (Colombia), used the GPRS protocol to send rain gauge data in real-time to a web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…The second is its built-in ability to fit into a star-based topology. The third is that, as argued by both Tadrist et al [ 62 ] and Ortega-Gonzalez et al [ 63 ], a LoRaWAN has demonstrated its robustness in adverse weather conditions, which usually go hand-in-hand with river flooding.…”
Section: Methodsmentioning
confidence: 92%
“…The second is its built-in ability to fit into a star-based topology. The third is that, as argued by both Tadrist et al [ 62 ] and Ortega-Gonzalez et al [ 63 ], a LoRaWAN has demonstrated its robustness in adverse weather conditions, which usually go hand-in-hand with river flooding.…”
Section: Methodsmentioning
confidence: 92%
“…An important reason for its use is to mitigate the impact on the population of natural hazards in vulnerable areas. EWS is an important tool for hazard risk management, and many applications require this solution to cope with phenomena such as tornadoes [17,18], floods [19,20], landslides [21,22], flash floods [23,24], tsunamis [25], and the like. Therefore, the use of emerging technologies in EWS is relevant and is a challenge for researchers.…”
Section: Emerging Technologies For Early Warning Systemmentioning
confidence: 99%
“…The technique was demonstrated using a simulation based on real data obtained from a hospital geriatric department in London, UK. The paper also discusses the possibility of applying the methodology to various medical departments (surgery, stroke, and mental illness) [38]. The study also proposed mathematical modeling to manage the bed occupancy in all departments of the hospital.…”
Section: Bed Occupancymentioning
confidence: 99%